Survey on Controlling an 8*8 led matrix with Bluetooth mobile and Arduino - Ahmed majid jaafar; Al-Hussein Mathar Abbas; Zain El Abidine Mohamed Hadi (Journal of Telecommunication Control and Intelligent System, 2021)
The purpose of this study is to examine the bulletin boards based on the matrix. System is attended to be interface with user by using Android application with Bluetooth, the user can send the content to be displayed in the matrix and then the message will be display and shifted. The main processing unit used is Atmega328 microcontroller which dedicated with Arduino UNO board, Shifts are used to measure, walk, and scroll through the screen to move text from right to left and vice versa, Bluetooth module is used to enable wireless network functionality and receiving feature. The system was developed in prototype circuit board and will explain it in detail on the chapter three.